Canarium patentinervium miq. (burseraceae kunth.): a phytochemical and pharmacological study - Rajagopal, Mogana Sundari (2014)
Canarium patentinervium Miq. belongs to the family of Burseraceae best known for producing resins of economic, medicinal, and cultural values such as frankincense, myrrh, and copal. This family consists of 18 genera and 700 species of trees. In the Asia-Pacific region, about 20 species of Burseraceae are used to treat haemorrhoids, heal wounds and to treat skin infections. This plant has been used to heal wounds amongst the indigenous people of Malaysia. Furthermore no pharmacological and phytochemical studies have been reported on this species. This study was undertaken to screen the phytochemical and pharmacological aspects of this plant. Qualitative phytochemical properties of the crude extract was determined for the presence of tannins, flavonoids, alkaloids, saponins or sterols. Phytochemical analysis of Canarium patentinervium Miq. revealed presence of tannins and flavonoids in the ethanol extract of leaves and barks. Bioassay guided fractionation led to isolation of eight secondary metabolites by chromatography which were identified by NMR techniques. Two coumarins (scopoletin and scoparone), five phenols (cynaroside, hyperin, (+)-catechin, lioxin and syringic acid) and a norsesquiterpene with cyclohexenone ring (vomifoliol). The latter three compounds were isolated for the first time from the genus Canarium. The plant and the isolated compounds were then subjected to six biological assays comprising of antibacterial, antioxidant, anticancer, anti-inflammatory, anti-acetylcholinesterase and anti-parasitic activities. Infectious diseases remain the leading cause of death worldwide and bacteria have become more resistant to conventional antibiotic and the search for novel antimicrobial agents from medicinal plants has become crucial. Antibacterial test was done using disc diffusion method, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and death kinetic assay with ampicillin as the positive control. The ethanol extract of leaves and the hexane extract of bark displayed remarkable antibacterial activity against both Gram-positive bacteria and Gram-negative bacteria. All isolated compounds tested against S.aureus ATCC 11632 showed bacterial growth inhibition. Scopoletin, scoparone, hyperin, cynaroside and syringic acid had bactericidal effect <100 µg/ml. Only scopoletin had bactericidal effect and complete kill at MBC 50.00 µg/ml. Bacterial infections have been known to generate extensive formation of free radicals which is becoming increasingly recognized in the pathogenesis of the many human diseases. The role of free radicals and active oxygen is becoming increasingly recognized in the pathogenesis of the many human diseases, including cancer, neurodegenerative diseases, ageing, and atherosclerosis. Five various antioxidant assays with different mode of action [2, 2-diphenyl-1-picrylhydrazyl (DPPH) and 2, 2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), ferric reducing antioxidant power (FRAP), β-carotene bleaching assay and superoxide dismutase (SOD) assay] were used to test the antioxidant scavenging abilities of this plant. Vitamin C (L-ascorbic acid), quercetin and trolox were used as positive controls. The ethanol extract of leaves and barks displayed superior antioxidant capacities. The EC50 values of the samples were consistently low in SET methods (ABTS, DPPH and FRAP) superior to standard as opposed to HAT method (β-carotene bleaching assay). Hyperin and (+)-catechin exhibited the most consistent free radical scavenging capability across the five antioxidant assay. Hyperin and (+)-catechin have significantly lower IC50 (0.75±0.03 µg/ml and 0.94±0.27 µg/ml respectively) compared to SOD enzyme (IC50 1.59±04 µg/ml). Scopoletin exhibited potent antioxidant activity compared to scoparone with significantly lower EC50 values in ABTS (IC50 1.08±0.03 µg/ml) compared to ascorbic acid (EC50 1.54±0.03 µg/ml) and lower values in FRAP assay (FRAP value 49.00±0.64 µg/ml) than quercetin (FRAP value 86.00±0.24 µg/ml) and ascorbic acid (FRAP value 347.00±0.23 µg/ml). Vomifoliol had potent β-carotene bleaching activity with IC50 6.85±0.37 µg/ml. Infections and free radical generation are recognized in the pathogenesis of cancer. The ethanol and chloroform extract of barks showed significant anticancer activities with GI50 values of 34.40µg/ml and 23.44µg/ml. The most susceptible cell lines were found to be the breast cancer cell line, MDA 468. Scopoletin displayed potent anticancer effect against breast cancer cell line MDA 468 (GI50 0.09±0.25 µg/ml) and colorectal cancer cell line HT-29 (GI50 0.17±0.05 µg/ml), the latter being more significant that positive control doxorubicin (GI50 0.66±0.60 µg/ml). In recent years, roles have been identified for several inflammatory cells and for a large number of inflammatory mediators in important pathologies not previously linked to inflammation, such as Alzheimer’s disease and cardiovascular disorders including atherosclerosis, as well as cancer. Recently, reports have appeared regarding so-called “dual inhibitors,” agents that inhibit not only cyclooxygenase-1 (COX-1) and cyclooxygenase-2 (COX-2), but also 5-lipoxygenase (5-LOX). Chloroform extract of the barks had the lowest 5-LOX inhibition (IC50=29.53±0.0 3μg/ml) when compared to NDGA (IC50=29.19±0.02 μg/ml). Ethanol extract of leaves had superior COX-1 inhibition (IC50 = 0.60±0.01µg/ml) compared to COX-2 inhibition (IC50 = 1.07±0.01 µg/ml), whereas the barks had superior COX-2 inhibition (IC50 = 9.39±0.03 µg/ml) as opposed to COX-1 (IC50 = 11.41±0.03 µg/ml). All isolated compounds exhibited significantly lower 5-LOX inhibition than NDGA. Scopoletin and scoparone were potent inhibitors of 5-LOX recording lowest IC50 values (IC50 0.34±0.01 µg/ml and 0.20±0.01 µg/ml respectively). However (+)-catechin had a more comprehensive anti-inflammatory activity with dual inhibition of 5-LOX (IC50 16.10±0.03 µg/ml) and COX (COX-1; IC50 12.08±0.02 µg/ml, COX-2; IC50 83.89±0.03 µg/ml). Syringic acid exhibited potent 5-LOX inhibition (IC50 1.38±0.03 µg/ml) and moderate COX-1 inhibition (IC50 34.89±0.02 µg/ml). Furthermore, oxidative and inflammatory processes are among the pathological features associated with the central nervous system in Alzheimer’s disease. There is evidence that acetyl cholinesterase (AChE) inhibitors have an anti-inflammatory role through action against free radicals and amyloid toxicity, as well as through decreasing release of cytokines from activated microglia in the brain and blood. Chloroform extract of the barks displayed the best activity (IC50 = 88.59±0.14 μg/ml) as opposed to positive control, galanthamine (IC50 = 0.74±0.06 μg/ml). The ethanol extract of barks and leaves follow through with IC50 = 186.00±0.15 μg/ml and IC50 = 201.24±0.15 μg/ml respectively. Only scopoletin, scoparone, vomifoliol and syringic acid showed AChE inhibition at IC50 <100 µg/ml. Syringic acid exhibited good AChE inhibition (IC50 29.53±0.19 µg/ml), lowest of all compounds tested. Choline is the precursor of phosphatidylcholine (PC), a main component of Leishmania promastigote membranes. Therefore, inhibition of choline formation may de¬crease Leishmania survival. This hypothesis can be tested by using inhibitors of the acetylcholinesterase enzyme (AChE), which catalyzes the hydrolysis of acetylcholine to choline and acetic acid, as leishmanicidal compounds. The hexane extract of leaves showed moderate antileshmanial activity with IC50 values of 257.40±0.30 μg/ml. Only ethanol extracts showed activity against Giardia intestinalis and Entamoeba histolytica at concentration of 500 μg/ml. Scopoletin was tested against all three parasite amd it was more potent against Leishmania donovani (IC50 163.30±0.32 µg/ml) and MIC of >200 µg/ml for both Giardia intestinalis and Entamoeba histolytica. Six kinds of major biological effects were evident in the crude and compounds namely, antioxidant, antibacterial, anti-inflammatory, anti-AChE, anti-parasitic, and anticancer all of which were reported for the first time from this plant. Given the aforementioned evidence it is tempting to speculate that Canarium patentinervium Miq. represents an exciting scaffold from which to develop leads for treatment of inflammatory and oxidative stress related diseases.